2013
DOI: 10.1155/2013/469505
|View full text |Cite
|
Sign up to set email alerts
|

Ehlers-Danlos Syndrome Type VIII: A Rare Cause of Leg Ulcers in Young Patients

Abstract: Ehlers-Danlos syndrome type VIII (EDS-VIII) is a very rare autosomal dominant disease characterized by early-onset periodontitis associated with features of Ehlers-Danlos syndrome. We report a 32-year-old man whose chronic leg ulcer led to the diagnosis of EDS-VIII. He had severe periodontitis with complete loss of permanent teeth and skin fragility with thin skin, atrophic scars, and brownish atrophic pretibial plaques. Leg ulcer is not a prominent feature of EDS-VIII. We suggest adding EDS-VIII to the list o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…Risk of bias for one publication (Rahman et al., ) was assessed as moderate, due to missing concise clinical and periodontal case descriptions. Pedigree analyses including one family ( n = 5; with sample sizes ranging from 2 to 12 affected individuals) (Biesecker, Erickson, Glover, & Bonadio, ; Nelson & King, ; Reinstein, Pariani, Lachman, Nemec, & Rimoin, ; Reinstein, Wang, Zhan, Rimoin, & Wilcox, ; Reinstein et al., ). Quality of all pedigree analysis was assessed as good (low risk of bias). Case reports ( n = 23; with sample sizes of one to two affected individuals)(Apaydin, ; Bond, Friend, & Meridith, ; Buckel & Zaenglein, ; Chen, Lee, Yu, & Chiang, ; Cikla, Sadighi, Bauer, & Baskaya, ; Cunniff & Williamson‐Kruse, ; Dyne, Vitellaro‐Zuccarello, Bacchella, Lanzi, & Cetta, ; Flachowsky, Tolkendorf, & Kamin, ; George et al., ; Hartsfield & Kousseff, ; Hoffman et al., ; Karrer, Landthaler, & Schmalz, ,b; Linch & Acton, ; Mataix, Banuls, Munoz, Bermejo, & Climent, ; McKusick, ; Moore, Votava, Orlow, & Schaffer, ; Perez, Al‐Shammari, Giannobile, & Wang, ; Riedl, Lost, Pontz, & Schofer, ; Ronceray et al., ; Slootweg & Beemer, ; Spranger, Spranger, Kirchhof, & Steinmann, ; Stewart, Hollister, & Rimoin, ). In two cases, respectively, two articles described the same individuals (Bond et al., ; Cunniff & Williamson‐Kruse, ; Karrer et al., ,b).…”
Section: Resultsmentioning
confidence: 99%
“…Risk of bias for one publication (Rahman et al., ) was assessed as moderate, due to missing concise clinical and periodontal case descriptions. Pedigree analyses including one family ( n = 5; with sample sizes ranging from 2 to 12 affected individuals) (Biesecker, Erickson, Glover, & Bonadio, ; Nelson & King, ; Reinstein, Pariani, Lachman, Nemec, & Rimoin, ; Reinstein, Wang, Zhan, Rimoin, & Wilcox, ; Reinstein et al., ). Quality of all pedigree analysis was assessed as good (low risk of bias). Case reports ( n = 23; with sample sizes of one to two affected individuals)(Apaydin, ; Bond, Friend, & Meridith, ; Buckel & Zaenglein, ; Chen, Lee, Yu, & Chiang, ; Cikla, Sadighi, Bauer, & Baskaya, ; Cunniff & Williamson‐Kruse, ; Dyne, Vitellaro‐Zuccarello, Bacchella, Lanzi, & Cetta, ; Flachowsky, Tolkendorf, & Kamin, ; George et al., ; Hartsfield & Kousseff, ; Hoffman et al., ; Karrer, Landthaler, & Schmalz, ,b; Linch & Acton, ; Mataix, Banuls, Munoz, Bermejo, & Climent, ; McKusick, ; Moore, Votava, Orlow, & Schaffer, ; Perez, Al‐Shammari, Giannobile, & Wang, ; Riedl, Lost, Pontz, & Schofer, ; Ronceray et al., ; Slootweg & Beemer, ; Spranger, Spranger, Kirchhof, & Steinmann, ; Stewart, Hollister, & Rimoin, ). In two cases, respectively, two articles described the same individuals (Bond et al., ; Cunniff & Williamson‐Kruse, ; Karrer et al., ,b).…”
Section: Resultsmentioning
confidence: 99%
“…pEDS was recognized as a distinct EDS subtype by Stewart, Hollister, & Rimoin, (), and the disease is characterized by severe periodontitis with early‐onset disease and premature loss of teeth, hyperpigmented scarring of pretibial areas, easy bruising and joint hypermobility. pEDS is an exceedingly rare subtype with autosomal dominant inheritance; to our knowledge, to date, only 23 case reports (McKusick, ; Stewart et al., ; Linch & Acton, ; Slootweg & Beemer, ; Riedl, Lost, Pontz, & Schofer, ; Flachowsky, Tolkendorf, & Kamin, ; Hartsfield & Kousseff, ; Hoffman et al., ; Bond, Friend, & Meridith, ; Dyne, Vitellaro‐Zuccarello, Bacchella, Lanzi, & Cetta, ; Apaydin, ; Cunniff & Williamson‐Kruse, ; Spranger, Spranger, Kirchhof, & Steinmann, ; Karrer, Landthaler, & Schmalz, 2000a; &b; Perez, Al‐Shammari, Giannobile, & Wang, ; Chen, Lee, Yu, & Chiang, ; Moore, Votava, Orlow, & Schaffer, ; Buckel & Zaenglein, ; Mataix, Banuls, Munoz, Bermejo, & Climent, ; Ronceray et al., ; Cikla, Sadighi, Bauer, & Baskaya, ; George et al., ), five simple family pedigree analyses (Biesecker, Erickson, Glover, & Bonadio, ; Nelson & King, ; Reinstein, Pariani, Lachman, Nemec, & Rimoin, ; Reinstein, Wang, Zhan, Rimoin, & Wilcox, ; Reinstein et al., ) and two large‐scale pedigree analyses (five or 17 families: Rahman et al., ; Kapferer‐Seebacher et al., ) of pEDS have been reported. In 2003, a genetic linkage study conducted in a five‐generation family with pEDS established disease mutation with chromosome 12p13 (Rahman et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…2). Histopathology demonstrated granulomatous changes indicative of necrobiosis lipoidica, rather than the nonspecific features of pEDS plaques 2 . Molecular genetic studies demonstrated a heterozygous variant (c.582+59>A) in intron 6 of the C0L3A1 gene, pathogenic in two patients with vEDS, affecting splicing, resulting in the skipping of exon 6 (p.Gly177_Pro194del), confirming vEDS, with coincident nondiabetic necrobiosis lipoidica and extensive dental disease of non‐periodontal origin.…”
Section: Figurementioning
confidence: 89%